Analisis Profil Tanah Di Sekitar Lahan Singkong, Gedung Laboratorium Terpadu Tidar - Anindira Sabila (Jurnal Pertanian Unggul, 2024)
Abstract A soil profile is a cross section of the soil body that shows the composition of the soil horizon starting from the top layer of soil to the bottom layer of the parent rock. Analyze the soil profile by emphasizing each soil layer which is differentiated through the color and texture of the soil by direct observation in the field. The results of the observations follow the soil profile blank guidelines starting from looking for data on general conditions of the place or land, identifying physical properties, and carrying out soil chemical properties tests to find out and determine the type of soil of a place based on the soil characteristics data obtained. Soil profiles provide benefits for the agricultural sector because they can help in choosing the right cultivation plants, managing soil fertility and soil quality, as well as utilizing good water/irrigation management for plant cultivation. Keywords – Soil Profile, Inceptisol Soil, Soil Physical Properties, and Soil Chemical Properties. Abstrak. Profil tanah merupakan suatu irisan melintang pada tubuh tanah yang menunjukkan susunan horison tanah dimulai dari permukaan tanah lapisan atas sampai lapisan bawah batuan induk. Menganalisis profil tanah dengan mempertegas setiap lapisan tanah yang dibedakan melalui warna dan tekstur tanah dengan pengamatan langsung di lapangan. Hasil pengamatan mengikuti pedoman blangko profil tanah dimulai dari mencari data kondisi umum tempat atau lahan, identifikasi sifat fisika, dan melakukan uji sifat kimia tanah untuk mengetahui dan menetukan jenis tanah suatu tempat berdasarkan data karakteristik tanah yang didapatkan. Profil tanah memberikan manfaat bagi bidang pertanian karena mampu membantu dalam memilih tanaman budidaya yang tepat, melakukan pengelolaan kesuburan tanah dan kualitas tanah, serta memanfaatkan pengelolaan air/irigasi yang baik untuk budidaya tanaman.   Kata Kunci – Profil Tanah, Tanah Inceptisol , Sifat Fisika Tanah, dan Sifat Kimia Tanah.